Protecting the Vulnerable: Child Custody Adjudication in Domestic Violence Cases in Banyuwangi Religious Court - Putri Maja Mulia Anisa; Tamam, Badrut; Alrawasdeh , Ziyad (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2024)
Domestic Violence (KDRT), which also often causes child custody disputes between two parents, is one of the many factors in divorce. Judges must consider the value of justice for each party when they decide a case. Building clear standards in assessing justice and dealing with social problems in the legal realm is difficult, especially when problems continue to arise in society, especially regarding child custody after divorce due to domestic violence. The method used in this research is empirical legal research, using legislative, conceptual, and legal psychology approaches. The results of this research are that the judge uses legal interpretation and legal principles based on Law Number 23 of 2002 article 2 letter b concerning Child Protection where